COASTAL PEOPLE'S BELIEF IN THE EFFECTIVENESS BETWEEN TRADITIONAL MEDICINE AND MODERN MEDICINE - Saragih, Dhea Fitri; Siregar, Putra Apriadi; Dalimunthe, Isnaini Alya Amanda; Andriani, Riski (Pusat Studi Gender dan Anak, 2024)
Traditional medicine in Indonesia, although modern medicine is easily available, is still the main choice of coastal communities because it is considered more powerful and effective and is a cultural heritage that has been used for generations. This study aims to determine how many coastal village communities use traditional medicine compared to modern medicine. This study used a qualitative method with a descriptive approach. The research population was the Tanjung Rejo Village community, and data were obtained through counseling and direct interviews with respondents. The research population was coastal village communities, with a focus on Tanjung Rejo Village. Respondents were drawn from the village population, with relevant sampling techniques to obtain representative data on the use of traditional and modern medicine. Based on the results of the study, it is known that the majority of people still use traditional medicine more often than modern medicine. They believe that traditional medicine is more potent and effective for treatment, especially since it has been used for generations in their neighborhood. The use of traditional medicine is still more dominant among coastal village communities because it is considered more effective and safe compared to modern medicine. It is recommended that further development and research into traditional medicine be conducted to increase its wider application.